2013
DOI: 10.2109/jcersj2.121.506
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the synthesis procedure of ultrafine monodispersed BaTiO<sub>3</sub> powders by solvothermal method

Abstract: Monodispersed BaTiO 3 nanoparticles with an average grain size of 35 nm were obtained by a convenient one-step solvothermal method. In this method, the crucial step to achieve ultrafine BaTiO 3 nanoparticles is the control of hydrolysis of Ti(OC 4 H 9 ) 4 by Diethylene glycol (DEG). DEG can strongly inhibit the hydrolysis procedure and prevent the grain growth of BaTiO 3 nanoparticles. Ba(OH) 2 ·8H 2 O provides H 2 O source and alkaline environment. Polyvinyl pyrrolidone (PVP) is used as surfactant. The as-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The existence of the OH group was confirmed by the FT-IR spectrum at room temperature. The weight loss at ∼320 • C was mainly caused by the combustion of PVP, as evidenced by the DTA peak [30]. For the sample that was prepared with a source ratio of [Ti]/[Ba] = 0.2 M:0.2 M, the weight of PVP adsorbed on the BT surface was estimated from the weight loss to be 4.1 wt%.…”
Section: Effect Of Koh Concentrationmentioning
confidence: 99%
“…The existence of the OH group was confirmed by the FT-IR spectrum at room temperature. The weight loss at ∼320 • C was mainly caused by the combustion of PVP, as evidenced by the DTA peak [30]. For the sample that was prepared with a source ratio of [Ti]/[Ba] = 0.2 M:0.2 M, the weight of PVP adsorbed on the BT surface was estimated from the weight loss to be 4.1 wt%.…”
Section: Effect Of Koh Concentrationmentioning
confidence: 99%
“…The final material exhibits different properties depending on the experimental conditions. As an example, Hao et al [45] synthesized monodispersed BaTiO 3 and studied the effect of different parameters on the growth-up mechanism of BaTiO 3 nanocrystals. Temperature, considered as the most important factor that influences the reaction, was studied and it was found that the increase of temperature leads to a decrease of grain size of BaTiO 3 nanopowders.…”
Section: Ii21 Hydro/solvothermal Synthesismentioning
confidence: 99%
“…[30][31] In this process, the precursors are put into a stainless steel autoclave and react under heating and pressure. [32] Hydrothermal synthesis method fabricates BaTiO3 particles with low dielectric loss at low synthesis temperature. [33] After 4 hours of reaction at 80 o C, BaTiO3 thin films are obtained by microwave hydrothermal synthesis method.…”
Section: Hydrothermal Synthesismentioning
confidence: 99%